2022
DOI: 10.3390/foods11213415
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin Induces Apoptosis and Suppresses Metastasis of Human Endometrial Carcinoma Ishikawa Cells via Endoplasmic Reticulum Stress Promotion and Matrix Metalloproteinase-2/9 Inhibition In Vitro and In Vivo

Abstract: Endometrial cancer (EC) is a very common female cancer which has attracted more and more attention. According to the individual patient’s condition, the current treatment of EC patients is mainly based on surgery, which is supplemented by chemotherapy, radiotherapy, and endocrine intervention. However, these existing treatment strategies also have some inevitable limitations. Therefore, it is particularly important to find an active ingredient with low toxicity and a high safety profile against EC. Isorhamneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Niclosamide (NIC) has emerged as a promising human endometrial cancer treatment by inducing Bax colocalization with lysosome and inhibiting Cathepsin B maturation from pro-cathepsin B, which induces lysosomal membrane permeability and releases hydrolase enzymes from the lysosome to cytosol, ultimately leading to cell death ( 122 ). Isorhamnetin is a flavonoid that affects ERS by modulating intracellular ROS levels, activating the endogenous mitochondrial apoptotic and exogenous death receptor pathways and ultimately inducing apoptosis, while inhibiting cell metastasis ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…Niclosamide (NIC) has emerged as a promising human endometrial cancer treatment by inducing Bax colocalization with lysosome and inhibiting Cathepsin B maturation from pro-cathepsin B, which induces lysosomal membrane permeability and releases hydrolase enzymes from the lysosome to cytosol, ultimately leading to cell death ( 122 ). Isorhamnetin is a flavonoid that affects ERS by modulating intracellular ROS levels, activating the endogenous mitochondrial apoptotic and exogenous death receptor pathways and ultimately inducing apoptosis, while inhibiting cell metastasis ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“… 44 Additionally, some studies have shown that kaempferol induces G2/M phase cell cycle arrest and apoptosis, inhibits cell invasion, and upregulates the m-TOR/PI3K signaling pathway, thus contributing to the suppression of endometrial cancer. 45 Furthermore, luteolin, 25 isorhamnetin, 46 artemetin, 25 and stigmasterol 47 have been found to inhibit the proliferation of endometrial cancer cells. Subsequently, we performed molecular docking of PTGS2 with quercetin, kaempferol, luteolin, isorhamnetin, artemetin, and stigmasterol and found that all of these components exhibited strong binding activity with PTGS2, with an affinity value smaller than −7.0 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that isorhamnetin exerted antitumor properties by activating the key proteins of mitochondria and ER-related pathways in EC cells [39]. Metformin inhibits the growth and survival of EC cells by inhibiting GRP78 and Wnt/β-catenin pathway [40].…”
Section: Discussionmentioning
confidence: 99%